2014
DOI: 10.1097/cmr.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Rare SF3B1 R625 mutations in cutaneous melanoma

Abstract: RNA splicing is the cellular process that has only recently been found to be an important target for various cancers. Among the spliceosome genes that are involved in cancers, SF3B1 is most frequently mutated. Recurrent mutation in codon 625 has been found in uveal melanoma, but this mutation has not been identified in cutaneous melanoma. We used whole-exome sequencing to explore the mutational landscape of 295 melanoma samples, 231 of which are cutaneous melanoma. Out of these cutaneous melanoma samples, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 9 publications
1
41
1
Order By: Relevance
“…2q33) have been reported in 1.8% of breast tumors, and more specifically in 4% of a subset of luminal breast tumors (Ellis et al 2012;Maguire et al 2015), and are significantly associated with the presence of estrogen-receptor (ER)-positive tumor cells, AKT1 mutations, and distinct copy-number alterations, including frequent chromosomal-segment gains on 16q12-q13 and 16q21-q22, and losses on 1p36-p35, 16q11-q13, and 16q21-q23 (Ellis et al 2012;Maguire et al 2015). SF3B1 mutations are also found at low frequency in pancreatic tumors (Biankin et al 2012), as well as melanoma (Furney et al 2013;Harbour et al 2013;Martin et al 2013;Kong et al 2014 ( Imielinski et al 2012). Interestingly, other splicing-factor mutations recurrent in blood malignancies, i.e., in SRSF2 or ZRSR2, have not yet been detected in solid tumors.…”
Section: Alterations In Splicing-factor Levels In Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2q33) have been reported in 1.8% of breast tumors, and more specifically in 4% of a subset of luminal breast tumors (Ellis et al 2012;Maguire et al 2015), and are significantly associated with the presence of estrogen-receptor (ER)-positive tumor cells, AKT1 mutations, and distinct copy-number alterations, including frequent chromosomal-segment gains on 16q12-q13 and 16q21-q22, and losses on 1p36-p35, 16q11-q13, and 16q21-q23 (Ellis et al 2012;Maguire et al 2015). SF3B1 mutations are also found at low frequency in pancreatic tumors (Biankin et al 2012), as well as melanoma (Furney et al 2013;Harbour et al 2013;Martin et al 2013;Kong et al 2014 ( Imielinski et al 2012). Interestingly, other splicing-factor mutations recurrent in blood malignancies, i.e., in SRSF2 or ZRSR2, have not yet been detected in solid tumors.…”
Section: Alterations In Splicing-factor Levels In Solid Tumorsmentioning
confidence: 99%
“…2). In addition, SF3B1 mutations of residues K700 and K666 have been reported in 1.8% of unselected breast tumors and 4% of luminal breast tumors (Ellis et al 2012;Maguire et al 2015), as well as in 3% of pancreatic ductal adenocarcinomas (Biankin et al 2012), whereas mutations of residues R625 and K666 are found in 15%-29% of uveal melanomas (Furney et al 2013;Harbour et al 2013;Martin et al 2013) and 1% of cutaneous melanomas (Table 1; Kong et al 2014).…”
Section: Recurrent Somatic Mutations Of Core Spliceosome Components Imentioning
confidence: 99%
“…Recurring hot spot mutations are found in myelodysplastic syndromes (Yoshida et al 2011), chronic lymphocytic leukemia (Landau et al 2013), chronic myelomonocytic leukemia (Patnaik et al 2013), uveal melanoma (Furney et al 2013), skin melanoma (Kong et al 2014), and breast (Ellis et al 2012) and pancreatic cancers (Biankin et al 2012). Spliceosome mutations are mutually exclusive and heterozygous and lead to missplicing of pre-mRNA to form aberrant transcripts.…”
mentioning
confidence: 99%
“…Importantly, these genes encode proteins that are all involved in 3 0 -splice site recognition during RNA splicing 4 . It has been shown that SF3B1 is mutated in a significant proportion (B20%) of uveal melanoma (UM), a rare malignant entity deriving from melanocytes from the uveal tract [5][6][7] , and in other solid tumours at lesser frequencies 8,9 .…”
mentioning
confidence: 99%